La mirada irónica de Kepa Garraza - Eguino, Naiara Herrera Ruiz de (2019)
Kepa Garraza (Berango, 1979) is an artist in whose artworks lies a very ironical charge, which is the central axis of these article. It approaches the essential characteristics of the ironic expressions, and from there it revises the pictorial series of Garraza. As a result, it will become apparent that the irony is one of the links between his series and it will also emphasize the ability of the pictorial images to take a critical and ironic character